2008
DOI: 10.2166/wst.2008.460
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism studies on chlorine and potassium permanganate degradation of microcystin-LR in water using high-performance liquid chromatography tandem mass spectrometry

Abstract: The presence of microystins (MCs) in water has the potential to harm people's health. In the MCs various isomers, MC-LR has the strongest toxicity and is the most harmful one. At present, several kinds of pre-oxidants, which are commonly used in water treatment process, are effective to remove MC-LR. However, it is still not clear about their degeneration mechanisms. Chlorine and potassium permanganate were selected in the present work since they are used worldwide for preoxidation treatment. Using the testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
(4 reference statements)
0
12
1
Order By: Relevance
“…Permanganate (MnO 4 – ; Mn­(VII)) is an oxidant used for the removal of organic contaminants, and offers advantages that include wide available pH conditions, ease of handling, relatively low oxidant demand, low cost, and absence of production of harmful byproducts (unlike ozone and chlorines). The oxidation of MCs by Mn­(VII) has been studied from various aspects, including the kinetics and mechanism of MC oxidation, effects of treatment conditions and water quality parameters, and toxicity changes. The literature has reported second-order rate constants for the reactions of representative MCs with Mn­(VII) ( k Mn(VII),MC ). Oxidation mechanisms have also been studied: dihydroxylation of alkene groups in Adda and Mdha moieties of MCs (refer to Figure ) was postulated as a primary oxidation mechanism, ,, which was further supported by mass spectrometry. , In addition, it has been demonstrated that the hepatotoxicity of MCs is effectively removed by Mn­(VII) oxidation . The effects of water quality parameters, such as pH, temperature, and organic and inorganic substances, have also been examined, showing that dissolved organic matter (DOM) is an important factor that affects the MC-LR oxidation rate by Mn­(VII). ,, …”
Section: Introductionmentioning
confidence: 96%
“…Permanganate (MnO 4 – ; Mn­(VII)) is an oxidant used for the removal of organic contaminants, and offers advantages that include wide available pH conditions, ease of handling, relatively low oxidant demand, low cost, and absence of production of harmful byproducts (unlike ozone and chlorines). The oxidation of MCs by Mn­(VII) has been studied from various aspects, including the kinetics and mechanism of MC oxidation, effects of treatment conditions and water quality parameters, and toxicity changes. The literature has reported second-order rate constants for the reactions of representative MCs with Mn­(VII) ( k Mn(VII),MC ). Oxidation mechanisms have also been studied: dihydroxylation of alkene groups in Adda and Mdha moieties of MCs (refer to Figure ) was postulated as a primary oxidation mechanism, ,, which was further supported by mass spectrometry. , In addition, it has been demonstrated that the hepatotoxicity of MCs is effectively removed by Mn­(VII) oxidation . The effects of water quality parameters, such as pH, temperature, and organic and inorganic substances, have also been examined, showing that dissolved organic matter (DOM) is an important factor that affects the MC-LR oxidation rate by Mn­(VII). ,, …”
Section: Introductionmentioning
confidence: 96%
“…Although chlorination treatment forms product due to the nucleophilic substitution reaction, still it might be believed that the formation rate of these hydroxylated products (linked to reduced toxicity) is accelerated using UV/chlorination treatment. Hence, Hybridized oxidation methods not only have potential to eliminate the toxicity level of the final solution but also promises to reduce the treatment period which is equally important for the drinking water plant (operational) perspective.A different perspective of reducing the microcystin toxicity apart from hydroxylation is the ability of MCs to form ketone by-products (keto-MCs)[117]. A DWTP which employs permanganate addition before chlorination (for disinfection), might change the requirement of chlorine dose demanded in excess to remove the cyanotoxins (or MCs).…”
mentioning
confidence: 99%
“…The pH value may play a decisive role during MC-LR removal because the structure and characteristics of both microgel-Fe(Ⅲ) and MC-LR were very dependent on it. Also, initial and final concentration of MC-LR treated by microgel-Fe(Ⅲ) or the isotherm study was also a key factor which should be considered first for different MC-LR removal methods (Feitz and Waite, 2003;Huang et al, 2008).…”
Section: 3mentioning
confidence: 99%